PERANAN POLIS ASURANSI JIWA DALAM PENUNTUTAN KLAIM (STUDI PADA PT. PRUDENTIAL LIFE ASSURANCE DENPASAR) - Gede Agung, Anak Agung; Dunia, Ngakan Ketut; Markeling, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 01, Februari 2014)
The title of this research is the role of law Life Insurance Policy In Prosecution Claims. Concerns about how the law consequent if the insured is unable to continue the life insurance premium payments to the insurance contract expires. In further description will be also discussed whether an insurance policy is an absolute requirement in the prosecution of insurance claims in the event of death of the insured risk. The purpose of this study was to determine the legal consequent if the insured is unable to continue the life insurance premium payments to the insurance contract expires. And to determine the role of the insurance policy in the prosecution of insurance claims in the event of death of the insured risk. Type used in this paper is an empirical legal research. Data collection techniques used are collecting secondary data and primary data. This type of approach used is collecting data from the field obtained from interviews and literature study. The conclusion of this study is the effect of law if it is not able to continue to pay premiums ends, the policy is considered void, but if the policy has a cash value so have a common alternative is to adopt appropriate policy cash value. And the insurance policy is not an absolute requirement in the prosecution of insurance claims in the event of death of the insured risk. Last premium payment receipt is a valid written evidence to prove that the insurance agreement has occurred.
Keywords: Insurance, Policy, Claims, Payment